Hemimegalencephaly: A rare congenital malformation of cortical development. Issue 12 (18th December 2021) - Jaiswal, Vikash; Hanif, Muhammad; Sarfraz, Zouina; Nepal, Gaurav; Naz, Sidra; Mukherjee, Dattatreya; Ruxmohan, Samir
Abstract: Hemimegalencephaly is a rare congenital malformation of cortical development usually associated with developmental delay and refractory epilepsy that sooner or later require hemispherectomy. Abstract : Hemimegalencephaly is a rare congenital malformation of cortical development usually associated with developmental delay and refractory epilepsy that sooner or later require hemispherectomy.